Gray matter volumes in patients with bipolar disorder and their first-degree relatives. Issue 2 (30th November 2015) - Nery, Fabiano G.; Gigante, Alexandre Duarte; Amaral, Jose A.; Fernandes, Francy B.F.; Berutti, Mariangeles; Almeida, Karla M.; Carneiro, Camila de Godoi; Duran, Fabio Luis Souza; Otaduy, Maria G.; Leite, Claudia Costa; Busatto, Geraldo; Lafer, Beny
Abstract: Bipolar disorder (BD) is highly heritable. First-degree relatives of BD patient have an increased risk to develop the disease. We investigated abnormalities in gray matter (GM) volumes in healthy first-degree relatives of BD patients to identify possible brain structural endophenotypes for the disorder. 3D T1-weighted magnetic resonance images were obtained from 25 DSM-IV BD type I patients, 23 unaffected relatives, and 27 healthy controls (HC). A voxel-based morphometry protocol was used to compare differences in GM volumes between groups. BD patients presented reduced GM volumes bilaterally in the thalamus compared with HC. Relatives presented no global or regional GM differences compared with HC. Our negative results do not support the role of GM volume abnormalities as endophenotypes for BD. Thalamic volume abnormalities may be associated the pathophysiology of the disease. Highlights: We investigated brain structure endophenotypes in bipolar disorder. We compared gray matter volumes in patients, their relatives, and controls. Patients presented smaller bilateral gray matter volumes than controls. Relatives did not differ from patients and controls on gray matter volumes. Abnormal gray matter volumes may not be an endophenotype for bipolar disorder.